Analisis Analisis Kelayakan Usaha Sayuran Sawi Hidroponik Di Kecamatan Kambu Kota Kendari - Syahria Rizka (Manajemen Agribisnis: Jurnal Agribisnis, 2022)
Farming using a hydroponic system really provides a solution to people in urban areas, hydroponics can be cultivated in a not so large area. This is started by the community or respondents in Kambu District by utilizing the land around the house. The mustard plant was chosen by the respondents to be cultivated because of its high demand and affordable selling price. This research was conducted to determine production costs, revenues, income, and the feasibility of a hydroponic mustard vegetable business in Kambu District, Kendari City. This research is a case study research on the hydroponic farming business of mustard greens in Kambu District, Kendari City. The results of this study indicate that the production costs incurred by respondents of hydroponic mustard vegetables in a year with a frequency of 8 harvests are Rp.256.000 mt-1 or Rp.3.072.000/year. The hydroponic mustard vegetable business that is run is feasible with an R-C value of 3.80 ratio with revenue and income in a year of Rp.11,704,000 and Rp. 8,632,000.